Where the state is not strong enough : what can army reconstruction tell us about change necessary to the OECD DAC SSR principles? - Robinson, Colin D. (Cranfield University, 2015)
Post-conflict army reconstruction is an important element of security sector reform (SSR), tracing its origins to at least 1980, before the SSR concept itself was formulated. Reconstruction of security forces is an important element in wider postconflict reconstruction, and for political reasons, an army has almost always deemed necessary. Since 1998, SSR itself has been increasingly conceptualized, with principles for SSR having been laid down by the Organization for Economic Cooperation and Development (OECD) since 2004. Yet SSR faces a host of philosophical and practical problems, perhaps the greatest being the gap between theory and practice (Chanaa's 'conceptual-contextual divide'). To make SSR efforts more successful, the underlying principles need to be revised and amended. Post-conflict army reconstruction experience since 1980, and associated academic study, military doctrine, and work by international organizations (particularly the OECD) can provide a basis for such revision. This thesis aims to survey post-conflict army reconstruction activities since 1980, draw overall lessons from that review and field study in Liberia, and propose amendments to the SSR principles on that basis.
© Cranfield University, 2011
Keywords: Post-conflict reconstruction; Security sector reform